2008
DOI: 10.1084/jem.20080829
|View full text |Cite
|
Sign up to set email alerts
|

Delta-like 4 is the essential, nonredundant ligand for Notch1 during thymic T cell lineage commitment

Abstract: The thymus is continuously seeded by progenitors derived from hematopoietic stem cells, which reside in the BM. These progenitors migrate via the blood stream into the thymus, where they adopt a T cell fate, proliferate, and diff erentiate into mature functional T cells. This differentiation process is characterized by multiple developmental stages. The earliest thymic progenitors lack surface expression of CD4 and CD8 and are therefore referred to as doublenegative (DN) thymocytes. They subsequently up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
318
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(343 citation statements)
references
References 37 publications
17
318
1
Order By: Relevance
“…In the mouse, it is well established that Notch1-DLL4 signaling is essential for inducing T cell differentiation in the immigrating T cell precursors (Wilson et al, 2001;Hozumi et al, 2008;Koch et al, 2008) and we believe that this interaction is also involved in inducing early T cell development in human. From our previous work, it is clear that Notch1 activation is responsible for inducing human T cell development ( Van de Walle et al, 2009, 2011, and although it remains to be clarified whether Delta-like 4 or Jagged2 is responsible for activating this receptor, the notion that a strong Notch signal is critical at this early stage of human T cell development ( Van de Walle et al, 2009) makes Delta-like 4 the most likely ligand .…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, it is well established that Notch1-DLL4 signaling is essential for inducing T cell differentiation in the immigrating T cell precursors (Wilson et al, 2001;Hozumi et al, 2008;Koch et al, 2008) and we believe that this interaction is also involved in inducing early T cell development in human. From our previous work, it is clear that Notch1 activation is responsible for inducing human T cell development ( Van de Walle et al, 2009, 2011, and although it remains to be clarified whether Delta-like 4 or Jagged2 is responsible for activating this receptor, the notion that a strong Notch signal is critical at this early stage of human T cell development ( Van de Walle et al, 2009) makes Delta-like 4 the most likely ligand .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the wild-type situation, the thymi of Foxn1 À/À ;Foxn1:Foxn4 mice contained large numbers of proliferating immature B cells ( Figures 6C and 6D), resembling the situation in the bone marrow (Hardy and Hayakawa, 2001) ( Figures S5A-S5C) and indicating the presence of intrathymic B cell poiesis. It is important to note that the hematopoietic phenotype of the thymi of Foxn1 À/À ;Foxn1:Foxn4 mice (that is, the coexistence of T and B cell poiesis) has not been previously observed in situations of impaired T cell development (Akashi et al, 2000;Ceredig, 2002;Hozumi et al, 2008;Koch et al, 2008;Wilson et al, 2001); for instance, the fraction of B cells in the thymus of Foxn1 À/À ;Foxn1:Foxn4 mice is far greater than that observed in T cell-deficient Cd3e À/À mice ( Figure S5D) and thus is not the result of a simple reduction of T cells in the thymus.…”
Section: Characteristics Of Foxn4-driven Hematopoietic Propertiesmentioning
confidence: 98%
“…It regulates the expression of key target genes such as those encoding the chemokine CXCL12, which is capable of attracting hematopoietic cells to the thymus (Calderó n and , and the NOTCH1 (Wilson et al, 2001) ligand DLL4, which directs T cell development (Hozumi et al, 2008;Koch et al, 2008;Calderó n and Boehm, 2012) in undifferentiated lymphoid progenitors. The essential role of FOXN1 in supporting thymopoiesis is illustrated by the failure of T cell differentiation in mammals lacking a functional Foxn1 gene (Frank et al, 1999;Nehls et al, 1994).…”
Section: Expression Patterns Of the Foxn1/4 Gene Family In Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of human thymopoeisis in culture have reported that Notch signaling regulates cell fate decisions in the T cell lineage in a dosedependent manner, suggesting that different levels of Notch signaling might be at play in different cell fate lineages that develop in the thymus [250]. The Notch ligand Dll4 is highly expressed in the thymic epithelial cells and activated Notch1 in the progenitors, driving T cell specification [251]. Loss of the repressor LRF in the hematopoietic progenitors leads to activation of Notch signaling in these cells and to differentiation of these cells into T cells in the bone marrow, as well as suppression of the B cell specification [252].…”
Section: The Mammalian Respiratory System: Notch Drives Differentiatimentioning
confidence: 99%